1989
DOI: 10.1016/0266-7681(89)90160-5
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of suture materials used in tendon surgery

Abstract: The following suture materials have been evaluated for their suitability for use in flexor tendon repairs: 4/0 gauge monofilament and multifilament stainless steel, mono-filament nylon, monofilament polypropylene, monofilament polybutestor, braided polyester, braided polyglycolic acid and a monofilament polyglyconate. These were investigated for their tensile strength (both knotted and unknotted), their extension to failure and knot-holding properties. Stainless steel and monofilament polyglyconate appeared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
83
3
9

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(98 citation statements)
references
References 13 publications
3
83
3
9
Order By: Relevance
“…When comparing the results with the literature for size 4-0 polypropylene, it was found that the force of approximately 6.75 Newtons presented here was much lower than the force of 13.76 Newtons presented by Trail et al [15].…”
Section: Discussioncontrasting
confidence: 46%
“…When comparing the results with the literature for size 4-0 polypropylene, it was found that the force of approximately 6.75 Newtons presented here was much lower than the force of 13.76 Newtons presented by Trail et al [15].…”
Section: Discussioncontrasting
confidence: 46%
“…If the cross-sectional area is increased, the gliding resistance through the pulley system is also increased [2,6,25]. [21] Therefore, if a robust knot is created (five throws) [34], gliding will be impeded. Second, it is possible that the knot is the weak point of the tendon repair because of decreased tensile strength of the suture [16,34].…”
Section: Discussionmentioning
confidence: 99%
“…[21] Therefore, if a robust knot is created (five throws) [34], gliding will be impeded. Second, it is possible that the knot is the weak point of the tendon repair because of decreased tensile strength of the suture [16,34]. Third, if the knot is located between the tendon ends, the apposition of the repair may be decreased [32].…”
Section: Discussionmentioning
confidence: 99%
“…For tendon sutures, the ideal suture is strong in the suture area and inelastic, with a low reactivity to stimulation that is also easy to handle while also having a safe knot 10 . There also must be minimal swelling in the suture area, and it must be strong enough to permit active movement in the early stages after suturing 11 .…”
Section: Discussionmentioning
confidence: 99%